Intracranial hemorrhage in infective endocarditis: A case report - Aziz, Fahad (Pioneer Bioscience Publishing Company, 2011)
Cerebral hemorrhage occurs rarely in infective endocarditis. Here, we present an interesting case of infective endocarditis complicated by sever cerebral hemorrhage. Later, his blood culture grew S bovis. To the best of our knowledge, this is the first ever reported case of S Bovis infective endocarditis complicated by extensive intracranial hemorrhage.